Carbonic anhydrase IX, a hypoxia-induced catalytic component of the pH regulating machinery in tumors - Sedlakova, Olga; Svastova, Eliska; Takacova, Martina; Kopacek, Juraj; Pastorek, Jaromir; Pastorekova, Silvia (Frontiers in Physiology, 2014)
Acidic tissue microenvironment contributes to tumor progression via multiple effects including the activation of angiogenic factors and proteases, reduced cell-cell adhesion, increased migration and invasion, etc. In addition, intratumoral acidosis can influence the uptake of anticancer drugs and modulate the response of tumors to conventional therapy. Acidification of the tumor microenvironment often develops due to hypoxia-triggered oncogenic metabolism, which leads to the extensive production of lactate, protons and carbon dioxide. In order to avoid intracellular accumulation of the acidic metabolic products, which is incompatible with the survival and proliferation, tumor cells activate molecular machinery that regulates pH by driving transmembrane inside-out and outside-in ion fluxes. Carbonic anhydrase IX (CA IX) is a hypoxia-induced catalytic component of the bicarbonate import arm of this machinery. Through its catalytic activity, CA IX directly participates in many acidosis-induced features of tumor phenotype as demonstrated by manipulating its expression and/or by in vitro mutagenesis. CA IX can function as a survival factor protecting tumor cells from hypoxia and acidosis, as a pro-migratory factor facilitating cell movement and invasion, as a signaling molecule transducing extracellular signals to intracellular pathways (including major signaling and metabolic cascades) and converting intracellular signals to extracellular effects on adhesion, proteolysis and other processes. These functional implications of CA IX in cancer are supported by numerous clinical studies demonstrating the association of CA IX with various clinical correlates and markers of aggressive tumor behavior. Although our understanding of the many faces of CA IX is still incomplete, existing knowledge supports the view that CA IX is a biologically and clinically relevant molecule, exploitable in anticancer strategies aimed at targeting adaptive responses to hypoxia and/or acidosis.